2020
DOI: 10.1155/2020/1475831
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Addition of Antioxidant Complex Packs and Functional Amino Acids Can Improve the Digestion, Absorption, and Immunity of Huanjiang Minipigs

Abstract: To study the effect of functional amino acids and the antioxidant function compound package on Huanjiang minipigs and to lay a foundation for the formulation of green and efficient feed for Huanjiang minipigs, we added functional amino acids and the antioxidant function compound package to piglet feed for 28 days. After feeding, we detected the growth performance, biochemical indexes, inflammatory indexes, and intestinal disaccharidase of piglets. It was found that functional amino acids and the antioxidant co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…Consistent with previous studies by Abbasi et al (2014) , Cui et al, 2020 , and Qiu et al (2022) , we have shown that carnosine precursor supplementation in the diet may affect the biochemical compounds in the jejunum.…”
Section: Resultssupporting
confidence: 92%
“…Consistent with previous studies by Abbasi et al (2014) , Cui et al, 2020 , and Qiu et al (2022) , we have shown that carnosine precursor supplementation in the diet may affect the biochemical compounds in the jejunum.…”
Section: Resultssupporting
confidence: 92%
“…Thus, maintaining the integrity and functions of intestinal barrier is essential for human and animal health [13] . The weaning stress of piglets can cause immune system destruction, intestinal microbiome dysbiosis, and intestinal barrier dysfunction, then leading to intestinal injury and poor health, thus reducing the growth performance, diarrhea occurrence, and even death [2,3,[33][34][35][36] . LPS is a component of the outer cell wall of Gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 99%